Manpower Planning, Work Environment and Service Delivery in Ogun State Hospital Management Board - Olanipekun, Lateef Okikiola (Zien Journals, 2021)
The problematic situation of developing societies to retain their medical personnel given their inability to institute viable manpower plan and conducive work environment that should be suitable for the fulfillment of the lofty aspirations of medical personnel is what necessitates the study. Hence, the study investigated the relationship between manpower planning, work environment and service delivery in Ogun State Hospital Management Board (OGHMB). Three hypotheses were formulated and tested for the study.
Keywords: relationship; conducive; environment; developing